Hubungan Antara Kepercayaan Diri dengan Body Image Remaja Perempuan Pengguna Media sosial Instagram - Boy Herdian; Hema Dayita (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aimed to determine the relationship between body image and self-confidence among adolescent female Instagram users in Bekasi City. Adolescence is a developmental period characterized by increased attention to physical appearance and intensive use of social media, which may influence individuals' perceptions of their bodies. A positive body image is believed to support the development of higher self-confidence, whereas a negative body image may contribute to lower self-confidence. This study employed a quantitative approach with a correlational research design. The population consisted of female adolescents aged 17–22 years who actively used Instagram and resided in Bekasi City. A purposive sampling technique was used to select 125 participants. The instruments used were a Body Image Scale based on Cash's theory and a Self-Confidence Scale based on Lauster's theory. Data were analyzed using Spearman's rho correlation test. The results showed a significant positive relationship between body image and self-confidence among adolescent female Instagram users (? = 0.6632; p 0.001). The correlation coefficient indicated a strong relationship between the two variables. These findings suggest that the more positive an adolescent's body image is, the higher her level of self-confidence. Conversely, a more negative body image is associated with lower self-confidence. Therefore, the research hypothesis was accepted, indicating that there is a positive and significant relationship between body image and self-confidence among adolescent female Instagram users.